The Effect of Management Ownership, Institutional Ownership, And Corporate Social Responsibility On Value Companies In Non Financial Companies Go Public On The Indonesia Stock Exchange - Adisty Ayu Lestari (International Journal of Applied Finance and Business Studies, 2021)
This study will investigate the influence of management ownership, institutional ownership, and corporate social responsibility to firm value. Firm value in this study as a proxy for the value of Tobin's Q. Collecting data using a purposive sampling method for non-financial companies listed in Indonesia Stock Exchange in 2011 until 2013. A total of 41 non-financial companies used as a sample. The method of analysis of this study used multiple regression. The results of this study indicate that the variable that affects the firm value is corporate social responsibility. While variables that did not affect the firm value is management ownership and institutional ownership.